Experimenting with Dimethyl Sulfoxide to Leach Gold from a Colombian Artisanal Gold Ore - Pariya Torkaman; Akihiro Yoshimura; Leslie M. Lavkulich; Marcello M. Veiga (Metals, 2023)
The diverse uses of gold and its crucial role in the global economy are growing, particularly during cycles of economic crises. The broad use of cyanide by conventional gold-mining companies and mercury by artisanal miners poses environmental and health concerns for local communities. This article introduces an innovative gold-leaching process using a non-toxic organic reagent, dimethyl sulfoxide (DMSO), a water-free lixiviant that extracts gold from ores/concentrates in combination with copper halides. The results of laboratory experiments using dimethyl sulfoxide and a sample of high-grade gold ore from Colombia show that 96.5% of the gold was extracted in 2 h at room temperature. The typical cyanidation process using 5 g/L of CN− at pH 10.5 on the same ore sample obtained 97% gold extraction in 24 h at ambient temperature. The gold extracted using DMSO was precipitated by adding a mild acidic solution, and the reagent can be recycled via distillation and reused in repeating cycles. The results show that DMSO can be used as a promising agent for gold leaching, offering a straightforward, cost-effective, and eco-friendly procedure with minimal chemical waste.